In vitro dissolution and bioavailability study of furosemide nanosuspension prepared using design of experiment (DoE) - Mohammad H. Shariare; Mohammad A. Altamimi; Akbar L. Marzan; Rahnuma Tabassum; Basarat Jahan; Hasan M. Reza; Mahbubur Rahman; G.U. Ahsan; Mohsin Kazi (Elsevier, 2019)
Background: Nanotechnology can offer the advantages of increasing solubility and bioavailability of delivering drugs like Furosemide. The aim of the current study is to investigate the in vitro and in vivo performance of furosemide nanosuspensions. Methods: Furosemide nanosuspensions were prepared by antisolvent precipitation method using full factorial experimental design. Four factors were employed namely; Stirring time, Injection rate, antisolvent: solvent ratio & stabilizer: drug ratio (at two levels = high & low). The in vitro dissolution experiments were conducted to compare the representative formulation with raw drug powder. The bioavailability of nanosuspension was, also, evaluated in mice as an animal model. Results: Solid state characterization (PXRD, DSC and FESEM) did show physical changes during preparation and optimization of the furosemide nanosuspensions. Individual material attributes showed more significant impact on the average particle size of the nanocrystals compared to process parameters. Two-way interactions between material attributes and process parameters significantly affected nanosuspension particle size distribution. Dissolution rate of furosemide nanosuspemsion was significantly higher than that observed for raw furosemide powder. The in vivo pharmacokinetics parameters of nanosuspension in comparison to pure drug showed significant increase in Cmax and AUC(0-t), about 233% and 266%, respectively. The oral bioavailability of furosemide from nanosuspension was about 2.3 fold higher as compared with the bioavailability from pure drug. Conclusions: Furosemide nanosuspensions prepared using antisolvent precipitation method enhanced the dissolution rate and oral bioavailability compared to raw furosemide powder. Keywords: Furosemide, Nanosuspension, Antisolvent precipitation, Stabilizer, In vitro in vivo assessment